Effects of Valerian and ST36 Acupuncture on Kidney and Liver Function in Rats - Seed Mohsin Al-Mosawei , Haneen; Luay Aziz , Batool; Mahmood Mousa Abo Almaali , Hassan (Pure Sciences International Journal of Kerbala, 2025)
Numerous dosages and formulations have been used in past studies of this ancient herbal sleep aid, valerian, utilizing a range of experimental methods. The purpose of this study is to assess how long-term valerian usage and acupuncture at ST36 affect kidney and liver function, with a focus on alterations in enzyme levels and general organ health. After the plant was ground, 4 g of the resulting powder was weighed and placed in a plastic container. The powder was then mixed with 100 milliliters of distilled water and left to steep for 15 minutes at 100°C. The mixture was then filtered through filter paper. After extracting four grams of the powdered plant material in 100 milliliters of distilled water at 100 degrees Celsius for fifteen minutes, the mixture was filtered. Rats were given the extract (40 mg/mL) orally at a dose of 400 mg/kg body weight (10 mL/kg).Before the experiment started, 32 rats (weighing 200–300 g) were kept in the lab for a week. Rats were housed in cages with free access to food and tap water. The Ethics Committee of Karbala University, Karbala, Iraq, authorized the experimental protocol and methods utilized in this study for the care and use of lab animals. The rats were randomly divided into four groups, each containing eight rats. No significant difference is noticed among study groups with control according to liver and kidney function tests (BUN, AST), except modest elevation of ALP in Valerian with acupuncture. Velerian extract did not significantly cause hepatorenal damage in rats under the study's settings. Biochemical indicators were not significantly changed by acupuncture at ST36, indicating a neutral modulatory impact.